2020
DOI: 10.2147/tcrm.s274122
|View full text |Cite
|
Sign up to set email alerts
|

Update on Safety Profiles of Vitamins B1, B6, and B12: A Narrative Review

Abstract: The neurotropic B vitamins B1 (thiamine), B6 (pyridoxine), and B12 (cobalamin) are essential for proper functioning of the nervous system. Deficiencies may induce neurological disorders like peripheral neuropathy (PN) and mainly occur in vulnerable populations (eg, elderly, diabetics, alcoholics). As epidemiologic cohort studies raised safety concerns about vitamin B6/B12 intake being potentially associated with increased risks of hip fracture (HF) and lung cancer (LC), we explored these aspects and performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 86 publications
0
16
0
2
Order By: Relevance
“…Due to the inconsistent curative effect and considering the adverse effect of high-dose vitamin B6, few studies were conducted to evaluate the potential efficacy. However, vitamin B6 is supposed that it works by promoting dopamine production and then activates dopamine receptors to reduce the secretion of pituitary prolactin [ 51 ], and the side-effects of high-dose vitamin B6 are fewer than expected [ 52 ], re-attempts of it are conducted recently and the results indicated that it could improve the AP-induced HPRL with few side-effects [ 30 , 53 ]. In our study, the results of NMA showed that this option might be a very effective method for the patients with AP-induced HPRL and provide a moderate certainly evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the inconsistent curative effect and considering the adverse effect of high-dose vitamin B6, few studies were conducted to evaluate the potential efficacy. However, vitamin B6 is supposed that it works by promoting dopamine production and then activates dopamine receptors to reduce the secretion of pituitary prolactin [ 51 ], and the side-effects of high-dose vitamin B6 are fewer than expected [ 52 ], re-attempts of it are conducted recently and the results indicated that it could improve the AP-induced HPRL with few side-effects [ 30 , 53 ]. In our study, the results of NMA showed that this option might be a very effective method for the patients with AP-induced HPRL and provide a moderate certainly evidence.…”
Section: Discussionmentioning
confidence: 99%
“…study design (prospective cohort study) and self-reporting by participants. Combined with the other studies reviewed, this led the authors to advise against changing intake recommendations for vitamin B6 (Calderon-Ospina et al, 2020). No newer studies have been identified to further clarify the association between a high intake of vitamin B6 and the risk of hip fracture.…”
Section: Risk Of Hip Fracturementioning
confidence: 99%
“…Given the frequency of deficiency, vitamin B supplementation is likely to be beneficial. As vitamin B is water soluble, long-term supplementation, even at high doses, is considered safe [ 134 ].…”
Section: Nutritional Therapy For Aldmentioning
confidence: 99%